A systematic review to identify research gaps in studies modeling MenB vaccinations against Neisseria infections - Soeren Metelmann; Alexander Thompson; Anna Donten; Segun Oke; Suzy Sun; Ray Borrow; Feng Xu; Roberto Vivancos; Valerie Decraene; Lorenzo Pellis; Ian Hall (PLoS ONE, 2025)
The genus Neisseria includes two major human pathogens: N. meningitidis causing bacterial meningitis/septicemia and N. gonorrhoeae causing gonorrhoea. Mathematical models have been used to simulate their transmission and control strategies, and the recent observation of a meningococcal B (MenB) vaccine being partially effective against gonorrhoea has led to an increased modeling interest. Here we conducted a systematic review of the literature, focusing on studies that model vaccination strategies with MenB vaccines against Neisseria incidence and antimicrobial resistance. Using journal, preprint, and grey literature repositories, we identified 52 studies that we reviewed for validity, model approaches and assumptions. Most studies showed a good quality of evidence, and the variety of approaches along with their different modeling angles, was assuring especially for gonorrhoea studies. We identified options for future research, including the combination of both meningococcal and gonococcal infections in studies to have better estimates for vaccine benefits, and the spill over of gonorrhoea infections from the heterosexual to the MSM community and vice versa. Cost-effectiveness studies looking at at-risk and the wider populations can then be used to inform vaccine policies on gonorrhoea, as they have for meningococcal disease.